Advanced data-analytics for power system security enhancement - Chen, Zhebin (Nanyang Technological University, 2024)
Security in power systems is of utmost importance to ensure the reliable and safe operation of electricity infrastructure. With the increasing integration of digital technologies and the advent of the smart grid, modern power systems infrastructure have become more interconnected and reliant on data communication networks. Nevertheless, they are also exposed to various cybersecurity threats and vulnerabilities at the same time.